Simulation Study of Wind Turbine System for Electric Powered Vehicle - Andias, Rino; Mohd, Sofian; Zulkafli, Fadhli; Hissein Didane, Djamal (International Journal of Integrated Engineering, 2020)
The present study investigated the airflow characteristics of wind turbine system to harness wind energy for electric powered pickup truck. The wind turbine consists of the rotating drag type rotor installed in the duct casing for wind concentrator. The geometry of the wind turbine system was modelled using SolidWorks software. The additional features of guide vane, additional outlet channel and second rotor blade were implemented to improvise the performance of previous design. CFD simulation work was conducted using commercial software of ANSYS Fluent. Initial inlet velocity were set for three different values i.e. 16.7m/s (60 km/h), 25m/s (90km/h) and 33.3m/s (120km/h). The results obtained indicated that the new design of duct casing with guide vane is capable to increase the air speed. The circulated air trapped in the duct casing which caused the negative torque of the rotor blade to occur were significantly reduced and increase the angular velocity as the additional outlet channel was introduced in the system. In addition, the implementation of double rotor blades in the modified design tends to increase the power generated by a factor of 1.5 as compared to the single rotor blade system.